2010
DOI: 10.1039/c002321c
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoro-functionalized PEDOT films with controlled morphology as superhydrophobic coatings and biointerfaces with enhanced cell adhesion

Abstract: Perfluoro-functionalized PEDOT thin films with various surface morphologies were prepared electrochemically by applying different potential pulse sequences using ionic liquids as electrolyte and solvent, and these films could display superhydrophobicity with enhanced capability of cell adhesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
1
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 25 publications
0
56
1
2
Order By: Relevance
“…In general, only a few cells can adhere on superhydrophobic surfaces, therefore decreasing their proliferative capacity [26,42]. In contrast, some studies have shown cell proliferation and survival [46,48] and in some cases even differentiation [47] and enhanced transfection efficiency [49]. But one also has to keep in mind that cell behavior can be cell type dependent [23,29].…”
Section: Cell Viability Adhesion and Proliferationmentioning
confidence: 98%
See 1 more Smart Citation
“…In general, only a few cells can adhere on superhydrophobic surfaces, therefore decreasing their proliferative capacity [26,42]. In contrast, some studies have shown cell proliferation and survival [46,48] and in some cases even differentiation [47] and enhanced transfection efficiency [49]. But one also has to keep in mind that cell behavior can be cell type dependent [23,29].…”
Section: Cell Viability Adhesion and Proliferationmentioning
confidence: 98%
“…Some authors reported higher cell affinity to rough surfaces [23,[46][47][48][49] and others the opposite [25,26,42,48]. In general, only a few cells can adhere on superhydrophobic surfaces, therefore decreasing their proliferative capacity [26,42].…”
Section: Cell Viability Adhesion and Proliferationmentioning
confidence: 99%
“…; 台盼蓝染色的 P19 细胞在不同 基底培养两天后的形态 [66] : (c)无培养基下的 PEDOT-OH 薄膜 [67] ; (d)无 培养基下的 PEDOT-F 薄膜 [67] ; (e)有培养基下的 PEDOT-OH 薄膜 [67] ;…”
Section: Figureunclassified
“…(f)有培养基下的 PEDOT-F 薄膜 [67] Figure 5 FM images of the MEF-GFP cells proliferation on (a) superhydrophobic and (b) superhydrophilic VACNTs surfaces, incubated for 6 d [66] ; Images of P19 cell stained with Trypan blue after two days in culture on (c) PEDOT-OH films in serum-free media [67] ; (d) PEDOT-F films in serum-free media [67] ; (e) PEDOT-OH films in serum-containing media [67] ; (f) PEDOT-F films in serum-containing media [67] 变氧等离子刻蚀时间制备出不同纳米粗糙度的超疏水 性聚苯乙烯(PS)表面, 并在其上进行了 Saos-2 细胞生长 实验. 结果发现, 光滑的 PS 表面可促进 Saos-2 细胞的 正常生长(图 6a, 6d, 6g), 而纳米尺度特别小的 PS 表面 却抑制细胞粘附(图 6b, 6e, 6h), 当纳米尺度增大时这种 效应会逐渐减弱(图 6c, 6f, 6i), 尽管此时表面仍呈现超 疏水.…”
Section: Figureunclassified
“…[1][2][3][4][5][6][7][8] Currently, superhydrophobic surfaces with water contact angles (CA) higher than 150 have received much attention. [9][10][11][12][13][14][15][16][17][18][19] The lotus leaf, with an ultrahigh CA but low water adhesion is demonstrated as the ideal water-repellent superhydrophobic surface and can show excellent self-cleaning properties.…”
Section: Introductionmentioning
confidence: 99%